Organization factors that influence transfer of training among employees at Farmers’ Organisation Authority (FOA) Headquarters, Kuala Lumpur / Roshidah Ahmad, Khulida Kirana Yahya and Iliyasu shiyanbade Najeemdeen - Ahmad, Roshidah; Yahya, Khulida Kirana; Najeemdeen, Lliyasu shiyanbade (Universiti Teknologi MARA, Shah Alam, 2019)
Transfer of training is important to organizations as they have devoted lot of money to send their employees for training to increase the employees’ knowledge, skills and abilities. This study aimed to examines the relationships of rewards, supervision, and peer relationship on the transfer of training involving employees at FOA Headquarters, Kuala Lumpur. Self-administered questionnaires were adapted from various sources and consisted of items related to transfer of training, rewards, supervision and peer relationships. A total of 344 questionnaires were distributed but only 265 were returned and used for further assessment. This study applied descriptive statistics, reliability and inferential analysis to examine the relationships among the variables. The results showed that only rewards and supervision had significant relationship with transfer of training while peer relationship was found to be insignificant.